Multiple Directorships and Financial and Non-Financial Reporting Measures: Evidence from Australia - Tham, Yeut Hong (Curtin University, 2016)
This thesis comprises three separate but connected essays focussing on multiple board directorships and its impact on financial and non-financial reporting measures of Australian publicly listed firms. Results suggest that financial reporting quality is enhanced with firms having skilled, knowledgeable and experienced board of directors resulting from other multiple board directorships. Consequently, the applicability of resource dependency theory between multiple directorships and earnings management, audit fees and CSR disclosures is validated from the results.